Pelatihan Mendeley untuk Memperkuat Basis Referensi Karya Ilmiah Mahasiswa Magister Ekonomi Syariah IAIN Tulungagung - Sujianto, Agus Eko (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Based on observations, not all Master of Islamic Economics Postgraduate students at IAIN Tulungagung understand and understand the greatness of the Mendeley application, so that the scientific work produced does not meet the writing standards, especially related to references. This Mendeley Application Training not only facilitates researchers in compiling a scientific paper, but also facilitates researchers in accessing quality references. This community service activity in the form of Mendeley training is here to answer the problems and dynamics that develop in Islamic Economics Masters students in compiling scientific papers. The training was held for 2 days, namely Wednesday, December 16, 2020 (class A) and Thursday, December 17, 2020 (class B). The division in 2 days of implementation is to further intensify the activities, because the training is carried out both theoretically and practically. The training results are divided into 2 parameters, namely the pre-test and post-test parameters. In the pre-test aspect, it turns out that the majority of students do not have the competence to run Mendeley. The results of the post-test, after participating in the training, students are able to carry out and implement it in the preparation of Mendeley-based scientific papers.